Studies of cholesterol structures in phospholipid bilayers - Carl S. Helrich (AIMS Biophysics, 2017)
Experiments and Monte Carlo (MC) simulations on ergosterol/nystatin channels providestrong evidence for superlattices in ergosterol/phospholipid planar bilayers. Monte Carlo simulationsalso revealed the presence of ergosterol superlattice domains in artificial vesicle membranes. MC simulation for ergosterol densities in these domains matched the dehydroergosterol (DHE) fluorescence measurements by Chong of dehydroergosterol density in multilamellar vesicles. Withergosterol/nystatin channels on the boundaries of these domains MC simulations produced agreement with experimental measurements of ergosterol/nystatin channel currents. These techniques, however, failed for cholesterol/nystatin channels. Although studies of initial dynamics in the formation ofergosterol/nystatin channels confirm ergosterol superlattices, they fail for cholesterol/nystatin channels. However a Fast Fourier Transform based study of the frequency of fluctuation spikes present inlow density cholesterol/nystatin channel currents revealed a dependence of spike frequency oncholesterol mol fraction which matched cholesterol density from DHE/cholesterol/DMPC fluorescence experiments. This indicates the probable presence of superlattices in cholesterol structures in phospholipid bilayers. The causal relationship between these statistical channel fluctuations andcholesterol structure is notable in its own right.